Controlling the bioactivity of a peptide hormone in vivo by reversible self-assembly. Issue 1 (December 2017) - Ouberai, Myriam; Santos, Ana; Kinna, Sonja; Madalli, Shimona; Hornigold, David; Baker, David; Naylor, Jacqueline; Sheldrake, Laura; Corkill, Dominic; Hood, John; Vicini, Paolo; Uddin, Shahid; et al.
Abstract The use of peptides as therapeutic agents is undergoing a renaissance with the expectation of new drugs with enhanced levels of efficacy and safety. Their clinical potential will be only fully realised once their physicochemical and pharmacokinetic properties have been precisely controlled. Here we demonstrate a reversible peptide self-assembly strategy to control and prolong the bioactivity of a native peptide hormone in vivo. We show that oxyntomodulin, a peptide with potential to treat obesity and diabetes, self-assembles into a stable nanofibril formulation which subsequently dissociates to release active peptide and produces a pharmacological effect in vivo. The subcutaneous administration of the nanofibrils in rats results in greatly prolonged exposure, with a constant oxyntomodulin bioactivity detectable in serum for at least 5 days as compared to free oxyntomodulin which is undetectable after only 4 h. Such an approach is simple, cost-efficient and generic in addressing the limitations of peptide therapeutics. The clinical potential of peptide therapeutic agents can only be fully realised once their physicochemical and pharmacokinetic properties are precisely controlled. Here the authors show a reversible peptide self-assembly strategy to control and prolong the bioactivity of a native peptide hormone in vivo.